Peran Moderasi Beragama Sebagai Kontrol Sosial Pada Mahasiswa Uin Sunan Kalijaga - Sari, Ramadhanita Mustika; Lestari, Vika Ayu (Jurnal Studi Agama, 2023)
This article discusses social control in UIN Sunan Kalijaga students. What is the role of religious moderation as social control in the modernization era and whether religious moderation has a role, especially for students at UIN Sunan Kalijaga who apply the concept of religious moderation which is quite thick. The research method used is a qualitative approach method, with the main data sources generated through short interviews and a google form. The supporting data source is in the form of library research data collection. The findings of the research show that there is a role of religious moderation as social control, which is a strategy in maintaining student behavior so that it is peaceful, tolerant, and respects one another's religion in the era of modernization in a renewal.